Rasional Emotive Behavior Theraphy (REBT) Dalam Membantu Mahasantri Ibnu Katsir 2 Jember Meningkatkan Regulasi Emosi - Maulida, Utari Putri; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Universitas Nusantara PGRI Kediri, 2024)
Human emotions can be categorized into two main types: pleasant and unpleasant feelings. Positive emotions, such as happiness and love, enhance well-being, while negative emotions, such as anger and sadness, can significantly impact individuals. This study aims to examine the effectiveness of Rational Emotive Behavior Therapy (REBT) in improving emotion regulation among students of Ibnu Katsir 2 Jember. The method used is a true experimental design with a pretest-posttest control group design, involving both experimental and control groups. The participants consist of 38 students selected through purposive sampling. Data analysis using t-test shows a significant difference between the two groups (p < 0.05), with the experimental group experiencing improved emotion regulation after the intervention. These findings confirm the effectiveness of REBT in reducing negative emotions and contribute to the field of guidance and counseling.